Humanistic Learning In The Digital Era: Balancing Technological Advancement And Educational Values - Maria Dina Mariana Malau; Windu Apiani; Kasmantoni; Adam Nasution; Hendro Ade Saputra (Amorti: Jurnal Studi Islam Interdisipliner, 2025)
The rapid advancement of digital technology has fundamentally transformed the landscape of education at various levels, including primary education based on Islamic elementary schools (Madrasah Ibtidaiyah). While technology offers easier access to information, diverse learning media, and greater efficiency, its unregulated use risks eroding the human dimension of education, such as personal interaction, empathy, and the cultivation of values. This study aims to comprehensively examine how the principles of humanistic learning can be preserved and balanced with the use of digital technology, particularly within the context of learning in Madrasah Ibtidaiyah and the competency development of prospective teachers in the Elementary Madrasah Teacher Education (PGMI) study program. This research employs a qualitative approach through library research, analyzing, comparing, and synthesizing more than seventeen literature sources consisting of national scholarly journal articles, reference books, and prior relevant studies. The findings indicate that humanistic learning in the digital era can be realized through four main pillars: positioning technology as a supporting tool rather than a replacement for the teacher's role; designing technology-based learning that remains student-centered; integrating religious and character values into every use of digital media; and strengthening teachers' digital literacy in balance with value-based literacy. This study recommends that the PGMI study program design a curriculum that equips prospective elementary madrasah teachers with integrated technological and humanistic-pedagogical competencies, so that technology does not replace the human touch in primary education.